Pengaruh Kompetensi Sumber Daya Manusia, Sistem Pengendalian Intern, dan Pemanfaatan Teknologi Informasi terhadap Kualitas Laporan Keuangan (Studi pada Badan Pusat Statistik Wilayah Maluku): The Influence of Human Resource Competence, Internal Control Systems, and Utilization of Information Technology on the Quality of Financial Reports (Study at the Central Statistics Agency for Maluku Region) - Gasperz, Jefry Jef (Universitas Muhammadiyah Sidoarjo, 2019)
This study aims to examine the effect of human resource competence, government internal control system and the use of information technology on the quality of financial statements of Central Bureau of Statistics in the Maluku Region.The population in this study are employees who handle accounting / financial reports on all accounting entities within the Central Bureau of Statistics in the Maluku Region.The research sample is the financial statements stylist includes PPK , PPSPM, financial staff, equipment, program development (planning) or administration as well as employees in the technical field who make financial reports. The data analyzed are primary data obtained through questionnaires. Total questionnaires distributed amounted to 57 and processed as many as 50 questionnaires (87.72%). The analytical method used is the multiple regression analysis method.Hypothesis testing results indicate that the competence of human resources and government internal control systems has a positive and significant effect on the quality of financial statements while the use of information technology has no effect on the quality of financial statements.